2007
DOI: 10.1007/s11916-007-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in tension-type headache

Abstract: The association between tension-type headache and cognitive ability was assessed among 971 members of a longitudinal birth cohort study. Primary headache status was determined at age 32 years according to 2004 International Headache Society criteria, frequent childhood headaches were identified from parent report from ages 7 to 13 years, and data relating to cognitive and academic performance from ages 3 to 32 years were analyzed. Adult study members with tension-type headache did not score worse on any of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In adults with tension type headache no cognitive dysfunction was identified [14]. The association between primary headaches and emotional and behavioral problems in children has been previously described [15,16], yet the prevalence of ADHD and learning disabilities among children with headaches as well as their association with headache duration and frequency is still contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…In adults with tension type headache no cognitive dysfunction was identified [14]. The association between primary headaches and emotional and behavioral problems in children has been previously described [15,16], yet the prevalence of ADHD and learning disabilities among children with headaches as well as their association with headache duration and frequency is still contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…On adult tension headache patients (TTH) there is only 1 longitudinal neuropsychological study that identified no cognitive impairments in TTH compared with M and C 20 …”
mentioning
confidence: 99%
“…TTH appears to have a signifi cant effect on cognitive measures, such as verbal and performance IQ, receptive language, and reading scores [43]. This correlation is stronger in the pediatric population than in adult headache sufferers.…”
Section: Pediatricsmentioning
confidence: 93%